Effects of steroid D-ring modification on suicide inactivation and competitive inhibition of aromatase by analogs of androsta-1,4-diene-3,17-dione - Sherwin, Paul F; McMullan, Patrick C; Covey, Douglas F (Journal of medicinal chemistry, 1989)
Analogues of androsta-1,4-diene-3,17-dione (3a) in which the D ring is modified were prepared and tested as suicide inactivators and competitive inhibitors of human placental aromatase. As long as the five-membered ring is intact, modifications of the D ring such as reduction or removal of the carbonyl group or conversion to a gamma-butyrolactone cause a less than 6-fold decrease in affinity for and rate of inactivation of aromatase, compared to 3a. Thus, an oxygen atom at C-17 is not required for binding of these inhibitors to aromatase, suggesting that hydrogen bonding to the D-ring oxygen does not play a major role in binding. Opening the D ring converts the cyclopentane ring to an alkyl chain and causes a greater than 300-fold decrease in affinity; this can be partially reversed by shortening the chain length. These results are consistent with a model in which the free chain of the opened D ring adopts conformations that sterically interfere with binding of the inhibitor to the enzyme. These findings may have practical applications in drug design, by allowing the preparation of 17-deoxo analogues that have high affinity for aromatase but that are not subject to reduction of the 17-carbonyl group, which is a major mode of metabolism of 3a.